Radiomimetic drug - â€˜Bleomycin’ induced DNA damage repair by Alstonia scholaris bark extracts â€“ A G2 assay based evidence - Chakraborty, Sumitra; Pithawala, Meonis (Innovare Journal of Life Sciences, 2019)
Objective: The present study initiated to know the probable DNA damage repair by A. scholaris extracts using Bleomycin-induced chemosensitive G2 assay in in-vitro cultured human blood lymphocytes. Methods: The plant extracts were from bark, stem and leaves and extraction solvents used were double distilled water and methanol. The experiments were carried out with blood samples collected from 12 healthy volunteers. A total of 28 culture vials from each individual were set up for lymphocyte cultures. These culture tubes (vials) were divided into two groups of fourteen each. The first group was labeled as â€˜G0' while the second as â€˜G2'. In both groups, initial vials (â€˜A') were kept untreated so as to act as a control, the second vial labeled (â€˜B') received treatment of an alone dose of BLM (15Î¼g/ml), while vials labeled â€˜C' to â€˜N' were treated with varied combinations. At the 71st hour, the cells were treated with 100 Î¼l of 0.001% colchicine. The cultures were terminated at the 72nd hour of incubation. Routine air-dried preparations were made. Each slide was blind coded, conveniently stained in 2% Giemsa and scored under 100X oil immersion lens. Results: The results indicated that aqueous as well as methanolic bark extracts had enough potential to repair DNA damage caused by Bleomycin. The extracts (both aqueous as well as methanolic) from stem or leaves were not that promising.Â Â